Molded body
Patent Information
- Application Number
- JP2021062280
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-03-31
AI Technical Summary
【0008】 本発明の成形体は、当該成形体の表面の算術平均粗さ(Ra)が、0を超え20μm未満である成形体であり、且つ耐傷性に優れ、柔軟で、且つ、サラサラ感があるので、自動車部品、土木·建材用品、電気·電子部品、衛生用品、フィルム·シート、発泡体、人造皮革など種々公知の用途に好適であり、特に自動車内装部品などの自動車部品、人造皮革などの表皮材に好適に用い得る。
Smart Images

Figure 0007633072000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a molded article, and more particularly to a molded article containing a thermoplastic elastomer composition. [Background technology]
[0002] Olefin-based thermoplastic elastomers are often used for interior skin materials such as instrument panels and door trims of automobiles, in order to reduce the weight of the materials. To mold interior skin sheets made of olefin-based thermoplastic elastomers into the shapes of instrument panels, door trims, etc., vacuum molding, particularly convex vacuum molding, is generally used. In convex vacuum molding, a mold without engraved texture is used, and a textured sheet with pre-applied texture is attached to the mold with the textured surface facing outward by vacuum suction to mold the sheet, so that the textured decorative pattern is easily destroyed. In particular, the textured decorative pattern of olefin-based thermoplastic elastomers is easily destroyed during vacuum molding, especially convex vacuum molding, compared to soft polyvinyl chloride resins, and the texture retention is poor, so there is a strong demand for improvement.
[0003] As an olefin-based thermoplastic elastomer with improved grain retention, Japanese Patent Laid-Open Publication No. 6-71751 (Patent Document 1) describes an olefin-based thermoplastic elastomer obtained by partially crosslinking a mixture of an olefin-based copolymer rubber having a Mooney viscosity of 80 to 350 at 100°C, an oil-extended olefin-based copolymer rubber, and an olefin-based polymer.
[0004] In addition, as thermoplastic elastomer compositions containing hydrogenated block copolymers having vinyl aromatic monomer units, a thermoplastic elastomer composition containing an ethylene-α-olefin copolymer and an olefin-based resin (Patent Document 2), and a thermoplastic elastomer composition containing a polypropylene-based resin, a softener, and a polyorganosiloxane (Patent Document 3) have been proposed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-71751 [Patent Document 2] International Publication No. 2010 / 067564 [Patent Document 3] International Publication No. 2011 / 155571 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to obtain a molded article which is excellent in scratch resistance, flexible, and has a smooth feel even when the surface of the molded article is subjected to a low unevenness embossing process. [Means for solving the problem]
[0007] The present invention relates to a molded article, at least a part of the surface of which is formed from a thermoplastic elastomer composition, and the arithmetic mean roughness (Ra) of the surface of the molded article is more than 0 and less than 20 μm. Effect of the Invention
[0008] The molded article of the present invention is a molded article having a surface with an arithmetic mean roughness (Ra) of more than 0 and less than 20 μm, and has excellent scratch resistance, flexibility, and a smooth feel. Therefore, the molded article is suitable for a variety of well-known applications such as automobile parts, civil engineering and building materials, electric and electronic parts, sanitary products, films and sheets, foams, and artificial leather, and can be particularly suitable for use in automobile parts such as automobile interior parts, and skin materials such as artificial leather. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0010] <Molded body> The molded article of the present invention is a molded article in which at least a portion of the surface of the molded article is formed from a thermoplastic elastomer composition and the surface of the molded article has a predetermined uneven shape, i.e., the arithmetic mean roughness (Ra) of the surface of the molded article is more than 0 and less than 20 μm.
[0011] A preferred embodiment for obtaining the above-mentioned molded article of the present invention will now be described. <Thermoplastic elastomer composition> The thermoplastic elastomer composition forming the molded article of the present invention is preferably a thermoplastic elastomer composition containing the following propylene polymer (A), the following ethylene-α-olefin copolymer (B), the following softener (C) and the following hydrogenated block copolymer (D), and is preferably a composition containing the following polyorganosiloxane (E).
[0012] The thermoplastic elastomer composition according to the present invention generally contains, relative to 100 parts by mass of the propylene polymer (A), 45 to 300 parts by mass, preferably 50 to 250 parts by mass, and more preferably 60 to 200 parts by mass of the ethylene-α-olefin copolymer (B), 45 to 300 parts by mass, preferably 45 to 290 parts by mass, and more preferably 50 to 280 parts by mass of the softener (C), and 100 to 400 parts by mass, preferably 100 to 280 parts by mass, and more preferably 120 to 250 parts by mass of the hydrogenated block copolymer (D).
[0013] When the thermoplastic elastomer composition according to the present invention contains the polyorganosiloxane (E), it is usually contained in an amount of 2 parts by mass or more, preferably 2.2 to 25 parts by mass, and more preferably 2.5 to 20 parts by mass, per 100 parts by mass of the propylene-based polymer (A).
[0014] The molded article made of the thermoplastic elastomer composition containing the polyorganosiloxane (E) has further improved scratch resistance. In the thermoplastic elastomer composition according to the present invention, the blending ratio (C / B) of the ethylene-α-olefin copolymer (B) to the softener (C) is preferably more than 0 and less than 3, more preferably more than 0.6 and not more than 2.8, and even more preferably more than 0.7 and not more than 2.5.
[0015] The thermoplastic elastomer composition according to the present invention preferably contains an organic peroxide (F) as necessary. The organic peroxide (F) according to the present invention acts as a crosslinking initiator for the propylene polymer (A) and the ethylene-α-olefin copolymer (B), which are components of the thermoplastic elastomer composition according to the present invention, by dynamically heat-treating the thermoplastic elastomer composition according to the present invention.
[0016] <Propylene-based polymer (A)> The propylene-based polymer (A) (hereinafter, sometimes referred to as "component (A)"), which is one of the components contained in the thermoplastic elastomer composition according to the present invention, refers to a polymer in which the content of constituent units derived from propylene among the constituent units constituting the polymer is 50 mol % or more, and the content of constituent units derived from propylene in component (A) is preferably 90 mol % or more.
[0017] The component (A) according to the present invention may be one type or two or more types. The component (A) according to the present invention may be a propylene homopolymer or a copolymer of propylene and a comonomer other than propylene.
[0018] The structure of component (A) according to the present invention is not particularly limited, and for example, the propylene-derived structural unit portion may be an isotactic structure, a syndiotactic structure, or an atactic structure, but is preferably an isotactic structure. In addition, in the case of the copolymer, it may be any of a random type (also called random PP), a block type (also called block PP: bPP), and a graft type.
[0019] The comonomer may be any other monomer copolymerizable with propylene, and is preferably an α-olefin having 2 or 4 to 10 carbon atoms. Specific examples include ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene, and among these, ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, and 1-octene are preferred. One type of comonomer may be used, or two or more types may be used.
[0020] The content of the structural units derived from the comonomer in the copolymer is preferably 10 mol % or less from the viewpoint of flexibility and the like. The component (A) according to the present invention may be synthesized by a conventionally known method, or a commercially available product may be used, such as polypropylene from Sunallomer Co., Ltd., Prime Polypro from Prime Polymer Co., Ltd., Novatec from Nippon Polypropylene Co., Ltd., and SCG PP from SCG Plastics.
[0021] The component (A) according to the present invention may be a crystalline polymer or a non-crystalline polymer, where crystalline means that a melting point (Tm) is observed in differential scanning calorimetry (DSC).
[0022] When the component (A) according to the present invention is a crystalline polymer, its melting point (based on the measurement method of JIS K 7121) is preferably 100°C or higher, more preferably 120°C or higher, and preferably 180°C or lower, more preferably 170°C or lower, from the viewpoint of heat resistance, etc.
[0023] The MFR (measured in accordance with the method of ASTM D 1238-65T, at 230° C. and under a load of 2.16 kg) of the component (A) according to the present invention is preferably 0.1 to 100 g / 10 min, and more preferably 0.1 to 50 g / 10 min.
[0024] By using the propylene-based polymer (A) having an MFR within this range, it is possible to obtain a thermoplastic elastomer composition suitable for obtaining a molded article having better scratch resistance, flexibility, and a smooth feel.
[0025] <Ethylene-α-olefin copolymer (B)> The ethylene / α-olefin copolymer (B), which is one of the components of the thermoplastic elastomer composition according to the present invention, is an ethylene / α-olefin copolymer containing units derived from ethylene and units derived from an α-olefin having 3 to 20 carbon atoms.
[0026] The ethylene-α-olefin copolymer (B) according to the present invention (hereinafter, sometimes referred to as "component (B)") can be obtained by copolymerizing at least ethylene and an α-olefin having 3 to 20 carbon atoms. Examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, and 1-dodecene. Among these, from the viewpoint of imparting flexibility, an α-olefin having 3 to 12 carbon atoms is preferred, propylene, 1-butene, and 1-octene are more preferred, and 1-octene is even more preferred.
[0027] Component (B) according to the present invention usually contains 70 to 99 mol %, preferably 80 to 97 mol %, of units derived from ethylene, and 1 to 30 mol %, preferably 3 to 20 mol %, of units derived from an α-olefin having 3 to 20 carbon atoms (wherein the total amount of units derived from ethylene and units derived from an α-olefin having 3 to 20 carbon atoms is taken as 100 mol %). The content ratio of units derived from ethylene within the above range is preferable for obtaining a thermoplastic elastomer composition suitable for obtaining a molded article having excellent mechanical strength characteristics.
[0028] Component (B) according to the present invention can be copolymerized with a monomer having an unsaturated bond, if necessary. As the monomer having an unsaturated bond, for example, conjugated diolefins such as butadiene and isoprene, non-conjugated diolefins such as 1,4-hexadiene, cyclic diene compounds such as dicyclopentadiene and norbornene derivatives, and acetylenes are preferable. Among these, ethylidene norbornene (ENB) and dicyclopentadiene (DCP) are more preferable from the viewpoint of flexibility of the obtained molded article.
[0029] The component (B) according to the present invention usually has an MFR (ASTM D1238, load 2.16 kg, temperature 190° C.) in the range of 0.1 to 20 g / 10 min, preferably 0.3 to 10 g / 10 min.
[0030] By setting the MFR within the above range, it is possible to obtain a thermoplastic elastomer composition suitable for obtaining a molded article having an excellent balance between flowability and mechanical strength. The component (B) according to the present invention usually has a density of 0.8 to 0.9 g / cm 3 is in the range.
[0031] The component (B) according to the present invention can be produced using a known polymerization catalyst, such as a Ziegler-Natta catalyst, a vanadium catalyst, or a metallocene catalyst. The polymerization method is not particularly limited, and can be carried out by a liquid phase polymerization method such as a solution polymerization method, a suspension polymerization method, or a bulk polymerization method, a gas phase polymerization method, or other known polymerization methods. In addition, these copolymers are not limited as long as they can achieve the effects of the present invention, and are also available as commercial products. Examples of commercial products include Engage 8842 (ethylene-1-octene copolymer) manufactured by Dow Chemical Company, Vistalon (registered trademark) manufactured by ExxonMobil Corporation, Esprene (registered trademark) manufactured by Sumitomo Chemical Co., Ltd., Mitsui EPT (registered trademark), Tafmer P (registered trademark), and Tafmer A (registered trademark) manufactured by Mitsui Chemicals, Inc.
[0032] <Softener (C)> The softener (C) (hereinafter, sometimes referred to as "component (C)"), which is one of the components of the thermoplastic elastomer composition according to the present invention, is not particularly limited, but plasticizers usually used for rubber can be used. From the viewpoint of compatibility with the propylene polymer (A) and the ethylene-α-olefin copolymer (B), etc., process oils consisting of paraffinic, naphthenic, aromatic, and other hydrocarbons are preferred. Among these components (C), process oils mainly consisting of paraffinic hydrocarbons are preferred from the viewpoint of weather resistance and colorability, and process oils mainly consisting of naphthenic hydrocarbons are preferred from the viewpoint of compatibility. From the viewpoint of thermal and light stability, the content of aromatic hydrocarbons in the process oil is preferably 10% or less, more preferably 5% or less, and even more preferably 1% or less, in terms of the carbon number ratio specified in ASTM D2140-97.
[0033] <Hydrogenated Block Copolymer (D)> The hydrogenated block copolymer (D), which is one of the components of the thermoplastic elastomer composition according to the present invention (hereinafter, sometimes referred to as "component (D)" or "hydrogenated product (D)"), is a hydrogenated block copolymer having at least one block mainly composed of conjugated diene monomer units and at least one block mainly composed of vinyl aromatic monomer units.
[0034] The component (D) according to the present invention is formed by hydrogenating (hereinafter sometimes referred to as "hydrogenation") at least a portion of the monomer units derived from a conjugated diene monomer. Here, the term "vinyl aromatic monomer unit" refers to a structural unit of a polymer resulting from polymerization of a vinyl aromatic compound monomer, and has a molecular structure in which two carbon atoms of a substituted ethylene group derived from a substituted vinyl group are bonded to each other. The term "conjugated diene monomer unit" refers to a structural unit of a polymer resulting from polymerization of a conjugated diene monomer, and has a molecular structure in which two carbon atoms of an olefin derived from the conjugated diene monomer are bonded to each other.
[0035] In the component (D) according to the present invention, the term "mainly composed of" means that the copolymer block contains 50% by mass or more, preferably 60% by mass or more, and more preferably 80% by mass or more of monomer units derived from a conjugated diene monomer (or a vinyl aromatic monomer) in the copolymer block. For example, a block mainly composed of conjugated diene monomer units means that the block contains 50% by mass or more, preferably 60% by mass or more, and more preferably 80% by mass or more of monomer units derived from a conjugated diene monomer.
[0036] The vinyl aromatic monomer in the component (D) according to the present invention is not particularly limited, and examples thereof include vinyl aromatic compounds such as styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, and N,N-diethyl-p-aminoethylstyrene. These may be used alone or in combination of two or more. Among these, styrene is preferred from the viewpoint of economic efficiency.
[0037] The conjugated diene monomer in the component (D) according to the present invention is a diolefin having a pair of conjugated double bonds, and examples thereof include 1,3-butadiene (butadiene), 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 1,3-hexadiene. Among these, butadiene and isoprene are preferred from the viewpoint of economic efficiency. These may be used alone or in combination of two or more.
[0038] The arrangement of each block in the component (D) according to the present invention is not particularly limited, and any suitable arrangement can be adopted. For example, when a polymer block consisting of vinyl aromatic monomer units is represented by S, and a polymer block consisting of units in which at least a part of the conjugated diene monomer units is hydrogenated is represented by B, the hydrogenated product of this block copolymer is represented by SB, S(BS). n1 (wherein n1 represents an integer of 1 to 3), S(BSB) n2(wherein n2 represents an integer of 1 to 2), and linear block copolymers represented by (SB) n3 X (wherein n3 is an integer of 3 to 6, and X is a coupling agent residue such as silicon tetrachloride, tin tetrachloride, or a polyepoxy compound). Among these, linear block copolymers of SB type 2 (diblock), SBS type 3 (triblock), and SBSB type 4 (tetrablock) are preferred.
[0039] Here, polymer block B may be a polymer block consisting of only conjugated diene monomer units, or a polymer block mainly containing conjugated diene monomer units and also containing vinyl aromatic monomer units (i.e., conjugated diene monomer units and vinyl aromatic monomer units are copolymerized), and in either polymer block, at least a portion of the conjugated diene monomer units are hydrogenated.
[0040] The content of the vinyl aromatic monomer unit in the component (D) according to the present invention is 30 to 80 mass%, and from the viewpoint of heat resistance and dispersibility, it is preferably 40 to 80 mass%, and more preferably 50 to 70 mass%. By making the content of the vinyl aromatic monomer unit 30 mass% or more, the mechanical properties can be further improved, and by making it 80 mass% or less, the low temperature properties can be further improved.
[0041] The content of vinyl aromatic monomer units in component (D) according to the present invention can be measured by nuclear magnetic resonance spectroscopy (NMR). The content of the vinyl aromatic monomer unit block in the component (D) according to the present invention is preferably 10% by mass or more, more preferably 10 to 40% by mass, from the viewpoint of mechanical strength. Here, the content of the vinyl aromatic compound polymer block in the component (D) is defined by the following formula using the mass of the vinyl aromatic compound polymer block (excluding vinyl aromatic compound polymers having an average degree of polymerization of about 30 or less) obtained by a method of oxidatively decomposing a copolymer before hydrogenation with tert-butyl hydroperoxide using osmium tetroxide as a catalyst (the method described in IM Kolthoff, et al., J. Polym. Sci. 1, 429 (1946), hereinafter also referred to as the "osmium tetroxide decomposition method"). Content of vinyl aromatic compound polymer block (mass%)=(mass of vinyl aromatic compound polymer block in copolymer before hydrogenation / mass of copolymer before hydrogenation)×100
[0042] When a plurality of polymer blocks are present in the component (D) according to the present invention, the structures such as molecular weight and composition of each may be the same or different. For example, a hydrogenated copolymer block containing a conjugated diene monomer unit and a vinyl aromatic monomer unit, and a hydrogenated copolymer block mainly composed of a conjugated diene monomer unit may be present in the component (D). The boundaries and ends of each block do not necessarily need to be clearly distinguished. The distribution mode of the vinyl aromatic monomer unit in each polymer block is not particularly limited, and may be uniform, tapered, stepped, convex, or concave. In addition, a crystalline portion may be present in the polymer block.
[0043] The mode of distribution of vinyl units of the conjugated diene monomer units in each polymer block in the component (D) according to the present invention is not particularly limited, and for example, the distribution may be biased. Methods for controlling the distribution of vinyl units include a method of adding a vinylizing agent during polymerization and a method of changing the polymerization temperature. In addition, the distribution of the hydrogenation rate of the conjugated diene monomer units may be biased. The distribution of the hydrogenation rate can be controlled by a method of changing the distribution state of the vinyl units, a method of copolymerizing isoprene and butadiene and then hydrogenating them using a hydrogenation catalyst described later, and utilizing the difference in the hydrogenation rate between the isoprene unit and the butadiene unit, and the like.
[0044] From the viewpoints of heat resistance, aging resistance and weather resistance, of the unsaturated bonds contained in the conjugated diene monomer units of the component (D) according to the present invention, preferably 75 mol % or more, more preferably 85 mol % or more, and even more preferably 97 mol % or more are hydrogenated.
[0045] The hydrogenation catalyst used is not particularly limited and is a conventionally known catalyst. (1) Supported heterogeneous hydrogenation catalysts in which metals such as Ni, Pt, Pd, and Ru are supported on carbon, silica, alumina, diatomaceous earth, etc. (2) So-called Ziegler type hydrogenation catalysts using transition metal salts such as organic acid salts or acetylacetone salts of Ni, Co, Fe, Cr, etc. and reducing agents such as organoaluminum, (3) Homogeneous hydrogenation catalysts such as organometallic compounds of Ti, Ru, Rh, Zr, etc., so-called organometallic complexes, can be used.
[0046] Specific examples of the hydrogenation catalyst that can be used include those described in JP-B-42-008704, JP-B-43-006636, JP-B-63-004841, JP-B-01-037970, JP-B-01-053851, JP-B-02-009041, etc. Among these, preferred hydrogenation catalysts include reducing organometallic compounds such as titanocene compounds.
[0047] As the titanocene compound, for example, the compounds described in JP-A-08-109219 can be used. Specific examples include compounds having at least one ligand having a (substituted) cyclopentadienyl skeleton, an indenyl skeleton or a fluorenyl skeleton, such as biscyclopentadienyltitanium dichloride and monopentamethylcyclopentadienyltitanium trichloride.
[0048] Examples of the reducing organometallic compound include organoalkali metal compounds such as organolithium compounds, organomagnesium compounds, organoaluminum compounds, organoboron compounds, and organozinc compounds.
[0049] The polymerization method of the block copolymer before hydrogenation in the component (D) according to the present invention is not particularly limited, and known methods can be adopted. For example, the methods described in JP-B-36-019286, JP-B-43-017979, JP-B-46-032415, JP-B-49-036957, JP-B-48-002423, JP-B-48-004106, JP-B-56-028925, JP-A-59-166518, JP-A-60-186577, etc. can be mentioned.
[0050] If necessary, component (D) may have a polar group. Examples of the polar group include a hydroxyl group, a carboxyl group, a carbonyl group, a thiocarbonyl group, an acid halide group, an acid anhydride group, a thiocarboxylic acid group, an aldehyde group, a thioaldehyde group, a carboxylate group, an amide group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, a phosphoric acid ester group, an amino group, an imino group, a nitrile group, a pyridyl group, a quinoline group, an epoxy group, a thioepoxy group, a sulfide group, an isocyanate group, an isothiocyanate group, a silicon halide group, an alkoxy silicon group, a tin halide group, a boronic acid group, a boron-containing group, a boronate salt group, an alkoxy tin group, and a phenyl tin group.
[0051] The vinyl bond content in the conjugated diene monomer unit in the block copolymer before hydrogenation in component (D) according to the present invention is preferably 5 mol% or more from the viewpoints of flexibility and scratch resistance, and is preferably 70 mol% or less from the viewpoints of productivity, elongation at break and scratch resistance. The vinyl bond content in the conjugated diene monomer unit is more preferably 10 to 50 mol%, even more preferably 10 to 30 mol%, and even more preferably 10 to 25 mol%.
[0052] The vinyl bond content herein means the ratio of 1,2-bonds and 3,4-bonds to the 1,2-bonds, 3,4-bonds and 1,4-bonds incorporated in the conjugated diene before hydrogenation. The vinyl bond content can be measured by NMR.
[0053] The weight average molecular weight of the component (D) before crosslinking is not particularly limited, but is preferably 50,000 or more from the viewpoint of scratch resistance, and is preferably 400,000 or less from the viewpoint of molding flowability, and more preferably 50,000 to 300,000. The molecular weight distribution (Mw / Mn: weight average molecular weight / number average molecular weight) is not particularly limited, but is preferably a value close to 1 from the viewpoint of scratch resistance. The weight average molecular weight and number average molecular weight can be determined by gel permeation chromatography (GPC; Shimadzu Corporation, device name "LC-10") using tetrahydrofuran (1.0 mL / min) as a solvent, at an oven temperature of 40°C, using TSKgelGMHXL (4.6 mmID x 30 cm, 2 columns). The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) are calculated as polystyrene equivalent molecular weights.
[0054] From the viewpoint of abrasion resistance, the block mainly composed of the conjugated diene monomer unit of the component (D) according to the present invention is preferably a copolymer block mainly composed of conjugated diene monomer units and also containing vinyl aromatic monomer units.
[0055] The component (D) according to the present invention is not particularly limited, and the above-mentioned conjugated diene monomers and vinyl aromatic monomers can be used. Among them, from the viewpoint of the balance between mechanical strength and impact resistance, preferred combinations include a block containing a butadiene unit and a styrene unit, a block containing an isoprene unit and a styrene unit, etc.
[0056] The component (D) according to the present invention may be any one that mainly contains at least a conjugated diene monomer unit, and the content of each monomer is not particularly limited. In particular, from the viewpoint of the balance between mechanical strength and impact resistance, the content of the vinyl aromatic monomer unit in the copolymer block is preferably 10% by mass or more and less than 50% by mass, more preferably 20% by mass or more and less than 50% by mass.
[0057] <Polyorganosiloxane (E)> The structure of polyorganosiloxane (E) (hereinafter, sometimes referred to as "component (E)"), which is one of the components that may be contained in the thermoplastic elastomer composition according to the present invention, is not particularly limited, but from the viewpoint of the abrasion resistance and feel of the molded product, it is preferable that the polyorganosiloxane has a linear, branched, or crosslinked polymer structure.
[0058] The component (E) according to the present invention is not particularly limited, and known ones can be used.Preferred polyorganosiloxane is a polymer containing siloxane units having a substituent such as an alkyl group, a vinyl group, or an aryl group, and among these, polyorganosiloxane having an alkyl group is particularly preferred, and polyorganosiloxane having a methyl group is more preferred.
[0059] Specific examples of polyorganosiloxanes having a methyl group include polydimethylsiloxane, polymethylphenylsiloxane, polymethylhydrogensiloxane, etc. Among these, polydimethylsiloxane is preferred.
[0060] The kinetic viscosity of the component (E) according to the present invention is not particularly limited, but from the viewpoint of abrasion resistance and scratch resistance, the kinetic viscosity (25°C) specified in JIS Z8803 is preferably 5000 centistokes (cSt) or more. In addition, from the viewpoint of tending to improve the dispersibility of the component (E) in the obtained thermoplastic elastomer composition, to provide an excellent appearance, and to further improve the quality stability during melt extrusion, the kinetic viscosity of the component (E) is preferably less than 3 million cSt. The kinetic viscosity of the component (E) is more preferably 10,000 cSt or more and less than 3 million cSt, and even more preferably 50,000 cSt or more and less than 3 million cSt.
[0061] <Organic peroxide (F)> Specific examples of the organic peroxide (F) according to the present invention include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)cyclododecane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)octane, n-butyl-4,4-bis(t-butylperoxy)butane, n-butyl-4 peroxyketals such as di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, α,α'-bis(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, and other dialkyl peroxides; acetyl peroxide, isobutyl diacyl peroxides such as aryl peroxide, octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,5,5-trimethylhexanoyl peroxide, benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, and m-trioyl peroxide; t-butyl peroxyacetate, t-butyl peroxyisobutyrate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxylaurate, t-butyl peroxybenzoate, and di-t-butyl peroxyacetate. peroxyesters such as t-butyl peroxyisophthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxymaleic acid, t-butyl peroxyisopropyl carbonate, and cumyl peroxyoctate; and hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, and 1,1,3,3-tetramethylbutyl peroxide.
[0062] Among these components (F), 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, and 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 are preferred from the viewpoints of thermal decomposition temperature, crosslinking performance, and the like.
[0063] The component (F) according to the present invention may be used alone or in combination of two or more kinds. When the thermoplastic elastomer composition according to the present invention contains component (F), the content thereof is preferably 2 to 6 parts by mass, more preferably 2 to 4 parts by mass, per 100 parts by mass of component (A) from the viewpoint of molding flowability. When the thermoplastic elastomer composition according to the present invention contains the component (F), it is preferable to use the following crosslinking aid in combination.
[0064] <Crosslinking aid> The crosslinking aid according to the present invention may be any of various known crosslinking aids, specifically, monofunctional monomers and polyfunctional monomers. Such crosslinking aids can control the crosslinking reaction rate.
[0065] As the monofunctional monomer, for example, a radically polymerizable vinyl monomer is preferable, and examples thereof include an aromatic vinyl monomer, an unsaturated nitrile monomer such as acrylonitrile or methacrylonitrile, an acrylic acid ester monomer, a methacrylic acid ester monomer, an acrylic acid monomer, a methacrylic acid monomer, a maleic anhydride monomer, and an N-substituted maleimide monomer.
[0066] Specific examples of monofunctional monomers include styrene, methylstyrene, chloromethylstyrene, hydroxystyrene, tert-butoxystyrene, acetoxystyrene, chlorostyrene, acrylonitrile, methacrylonitrile, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, 2-ethylhexyl methacrylate, maleic anhydride, methylmaleic anhydride, 1,2-dimethylmaleic anhydride, ethylmaleic anhydride, phenylmaleic anhydride, N-methylmaleimide, N-ethylmaleimide, N-cyclohexylmaleimide, N-laurylmaleimide, and N-cetylmaleimide. Among these, styrene, acrylonitrile, methacrylonitrile, methyl acrylate, maleic anhydride, and N-methylmaleimide are preferred from the viewpoint of ease of reaction and versatility. These monofunctional monomers may be used alone or in combination of two or more.
[0067] The polyfunctional monomer is a monomer having a plurality of radically polymerizable functional groups as functional groups, and is preferably a monomer having a vinyl group. The number of functional groups of the polyfunctional monomer is preferably 2 or 3.
[0068] Specific examples of the polyfunctional monomer include divinylbenzene, triallyl isocyanurate, triallyl cyanurate, diacetone diacrylamide, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, diisopropenylbenzene, p-quinone dioxime, p,p'-dibenzoylquinone dioxime, phenylmaleimide, allyl methacrylate, N,N'-m-phenylene bismaleimide, diallyl phthalate, tetraallyloxyethane, and 1,2-polybutadiene, and more preferably divinylbenzene and triallyl isocyanurate. These polyfunctional monomers may be used alone or in combination of two or more.
[0069] When the thermoplastic elastomer composition according to the present invention contains a crosslinking aid, the amount of the crosslinking aid is 1 to 100 parts by mass, preferably 1 to 50 parts by mass, per 100 parts by mass of component (F). The thermoplastic elastomer composition according to the present invention may contain, in addition to the above-mentioned component (A), an inorganic filler, a plasticizer, and other additives.
[0070] Examples of the inorganic filler include calcium carbonate, magnesium carbonate, silica, carbon black, glass fiber, titanium oxide, clay, mica, talc, magnesium hydroxide, and aluminum hydroxide.
[0071] Examples of the plasticizer include polyethylene glycol, phthalate esters such as dioctyl phthalate (DOP), and the like. Other additives include, for example, organic and inorganic pigments such as carbon black, titanium dioxide, and phthalocyanine black; heat stabilizers such as 2,6-di-t-butyl-4-methylphenol and n-octadecyl-3-(3,5'-di-t-butyl-4-hydroxyphenyl)propionate; antioxidants such as trisnonylphenylphosphite and distearyl pentaerythritol diphosphite; ultraviolet absorbers such as 2-(2'-hydroxy-5'methylphenyl)benzotriazole and 2,4-dihydroxybenzophenone; bis-[2,2,6,6-tetramethyl-4-piperidinyl]sebacate, tetrakis(tetramethylphenyl)propionate, and the like. Examples of suitable antibacterial agents include light stabilizers such as (2,2,6,6-tetramethyl-4-piperidinyl)-1,2,3,4-butanetetracarboxylate; flame retardants such as ammonium polyphosphate, trioctyl phosphate, and magnesium hydroxide; silicone oils such as dimethyl silicone oil and methylphenyl silicone oil; antiblocking agents such as stearic acid amide and erucic acid amide; foaming agents such as sodium bicarbonate and N,N'-dinitrosopentamethylenetetramine; antistatic agents such as palmitic acid monoglyceride and stearic acid monoglyceride; and antibacterial agents such as silver ion-supported zeolite and silver thiosulfite complex.
[0072] <Production method and properties of thermoplastic elastomer composition> The thermoplastic elastomer composition according to the present invention is dynamically crosslinked to crosslink at least a part of the components (A), (B) and (D) (for example, at least a part of the component (B)) contained in the thermoplastic elastomer composition. When performing dynamic crosslinking, it is preferable to dynamically heat treat the composition in the presence of the component (F) or in the presence of the component (F) and the crosslinking coagent.
[0073] In the present invention, the term "dynamic heat treatment" refers to kneading in a molten state. With respect to the thermoplastic elastomer composition according to the present invention, the composition before being dynamically heat-treated is also called "composition 1", and the composition after being dynamically heat-treated is also called "composition 2".
[0074] The dynamic heat treatment in the present invention is preferably carried out in a non-open type apparatus, and is preferably carried out under an inert gas atmosphere such as nitrogen or carbon dioxide gas. The heat treatment temperature is in the range of from the melting point of component (A) to 300°C, and is usually 150 to 270°C, and preferably 170 to 250°C. The kneading time is usually 1 to 20 minutes, and preferably 1 to 10 minutes. The applied shear force, expressed as a shear rate, is usually 10 to 50,000 s -1 , preferably 100 to 10,000 s -1 is in the range.
[0075] The Shore A hardness (10 second value) of Composition 2 (based on the measurement method of JIS K 6253) is preferably 30-75, more preferably 40-73, and further preferably 50-70.
[0076] When the Shore A hardness (10-second value) of composition 2 is within the above range, a molded article having design properties such as a good feel and a luxurious appearance, and scratch resistance can be easily formed, and the obtained molded article has particularly excellent scratch resistance.
[0077] Specifically, the Shore A hardness (10-second value) can be measured by the method described in the following examples. The melt flow rate of composition 2 (measured in accordance with JIS K 7210, at 230°C and under a load of 1.2 kg) is 0.1 to 100 g / 10 min, more preferably 5 to 90 g / 10 min, and even more preferably 10 to 80 g / 10 min, in order to provide a composition with excellent moldability.
[0078] <Molded body> The molded article of the present invention is a molded article in which at least a portion of the surface of the molded article is formed from a thermoplastic elastomer composition and the surface of the molded article has a predetermined uneven shape, i.e., the arithmetic mean roughness (Ra) of the surface of the molded article is more than 0 and less than 20 μm. The arithmetic mean roughness (Ra) of the surface of the molded article is preferably more than 0 and 15 μm or less, more preferably 2 to 13 μm, and even more preferably 3 to 10 μm or less. When the arithmetic mean roughness (Ra) of the surface of the molded article is within the above range, the molded article has excellent surface scratch resistance and tactile feel (smooth feel).
[0079] The molded article of the present invention is a molded article molded by any known molding method according to the use of the molded article. Examples of the molding method include press molding, injection molding, extrusion molding, calendar molding, hollow molding, vacuum molding, and compression molding. From the viewpoint of productivity and easy formation of complex shapes, it is preferable that the molded article is an injection molded article molded by injection molding.
[0080] In addition to the above-mentioned properties, the molded article of the present invention has low hardness, flexibility, and excellent scratch resistance, and is not particularly limited in its applications. It is suitable for a variety of well-known applications, such as automobile parts, civil engineering and building materials, electric and electronic parts, sanitary products, films and sheets, foams, and artificial leather, and can be particularly suitable for use in automobile parts such as automobile interior parts, and skin materials such as artificial leather.
[0081] <Automobile parts> Examples of automobile parts for which the molded article of the present invention can be used include weather strips, ceiling materials, interior seats, bumper moldings, side moldings, air spoilers, air duct hoses, cup holders, side brake grips, shift knob covers, seat adjustment knobs, flapper door seals, wire harness grommets, rack and pinion boots, suspension cover boots, glass guides, inner belt line seals, roof guides, trunk lid seals, molded quarter window gaskets, corner moldings, glass encapsulations, hood seals, glass run channels, secondary seals, various packings, bumper parts, body panels, side shields, glass run channels, instrument panel skins, door skins, ceiling skins, weather strip materials, hoses, steering wheels, boots, wire harness covers, and seat adjuster covers. Among these, the thermoplastic elastomer composition of the present invention is particularly preferred because it can improve the texture and feel.
[0082] <Civil engineering / building materials supplies> Examples of civil engineering and building materials in which the molded article of the present invention can be used include civil engineering and building materials such as ground improvement sheets, water supply boards, and noise prevention walls, various gaskets and sheets for civil engineering and construction, water stop materials, joint materials, and architectural window frames. Among these, the molded article of the present invention is particularly preferred because it can improve the texture and feel.
[0083] <Electrical and electronic parts> Examples of electric and electronic parts for which the molded article of the present invention can be used include electric wire coating materials, connectors, caps, plugs, and other electric and electronic parts. Among these, the molded article of the present invention is particularly preferred because it can improve the texture and feel.
[0084] Daily necessities Examples of daily necessities in which the molded article of the present invention can be used include sports goods such as sports shoe soles, ski boots, tennis rackets, ski bindings, and bat grips, as well as miscellaneous goods such as pen grips, toothbrush grips, hair brushes, fashion belts, various caps, and shoe inner soles. Among these, the molded article of the present invention is particularly preferred because it can improve the texture and feel.
[0085] <Films and Sheets> Examples of films and sheets that can be used in the form of the present invention include infusion bags, medical containers, automobile interior and exterior materials, beverage bottles, clothing cases, food packaging materials, food containers, retort containers, pipes, transparent substrates, sealants, etc., and among these, the molded articles of the present invention are particularly preferred because they can improve the texture and feel.
[0086] <Artificial leather> Examples of artificial leather that can be used with the molded product of the present invention include chair coverings, bags, school bags, sports shoes such as track and field shoes, marathon shoes, and running shoes, clothing such as jackets and coats, obi, sashes, ribbons, notebook covers, book covers, key chains, pen cases, wallets, business card holders, and pass holders, of which the molded product of the present invention is particularly preferred because it can improve the texture and feel of leather. EXAMPLES
[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. The test methods for each component of the raw materials used in the examples and comparative examples are as follows.
[0088] (1) Hydrogenation rate (%) The hydrogenation rate was measured by nuclear magnetic resonance spectroscopy (NMR). A nuclear magnetic resonance measuring device (manufactured by JEOL, device name "JNM-LA400") was used as the measuring device, deuterated chloroform was used as the solvent, and tetramethylsilane (TMS) was used as the chemical shift standard. The measurement was performed under the conditions of a sample concentration of 50 mg / mL, an observation frequency of 400 MHz, a pulse delay of 2.904 seconds, a scan count of 64 times, a pulse width of 45°, and a measurement temperature of 26°C.
[0089] (2) Content of monomer units and bond units The contents of vinyl aromatic monomer units, ethylene monomer units, butylene monomer units, 1,4-bond units, 1,2-bond units and 3,4-bond units of butadiene were measured by NMR. A nuclear magnetic resonance measuring device (manufactured by JEOL, device name "JNM-LA400") was used as the measuring device, deuterated chloroform was used as the solvent, and tetramethylsilane (TMS) was used as the chemical shift standard. The measurement was performed under the conditions of a sample concentration of 50 mg / mL, an observation frequency of 400 MHz, a pulse delay of 2.904 seconds, a scan count of 64 times, a pulse width of 45° and a measuring temperature of 26°C.
[0090] The mass fraction (mass%) of each structural unit contained in component (B) is 13 Specifically, the C-NMR of copolymer (B-1) was measured using an ECX400P nuclear magnetic resonance spectrometer (manufactured by JEOL Ltd.) under the conditions of a measurement temperature of 120° C., a measurement solvent of orthodichlorobenzene / deuterated benzene=4 / 1 (volume ratio), and an accumulation number of 8000. 13 Calculated from the C-NMR spectrum.
[0091] (3) Styrene polymer block content (Os value) The styrene polymer block content was measured by the method (osmium tetroxide decomposition method) described in IM Kolthoff, et al., J. Polym. Sci. 1, 429 (1946) using the copolymer before hydrogenation. A 0.1 g / 125 mL tertiary butanol solution of osmic acid was used to decompose the copolymer before hydrogenation. The styrene polymer block content was calculated by the following formula. The styrene polymer block content obtained here is referred to as the "Os value". Styrene polymer block content (Os value; mass%) = [(mass of styrene polymer block in copolymer before hydrogenation) / (mass of copolymer before hydrogenation)]×100
[0092] (4) Peak temperature of loss tangent (tan δ) The viscoelasticity was determined by measuring the viscoelasticity spectrum using a viscoelasticity measurement analyzer (ARES, manufactured by Ta Instruments) under conditions of strain of 0.1% and frequency of 1 Hz. In the examples and comparative examples, the following polymers were used.
[0093] [Propylene-based polymer (A)] As the propylene polymer (A-1), a propylene homopolymer (homo PP) (trade name: SunAllomer (registered trademark) PL400A, manufactured by SunAllomer Co., Ltd.) having a melt flow rate (MFR) of 2.0 g / 10 min at 230° C. and a load of 2.16 kg was used.
[0094] [Ethylene-α-olefin copolymer (B)] As the ethylene-α-olefin copolymer (B-1), an ethylene-1-octene copolymer (Dow Chemical Company, trade name "Engage 8842") was used. The ethylene content of the copolymer was 55% by mass, the octene content was 45% by mass, and the MFR measured under the conditions of temperature: 190°C, load: 2.16 kg was 1.0 g / 10 min.
[0095] [Softener (C)] As the softener (C-1), a paraffin-based oil (manufactured by Idemitsu Kosan Co., Ltd., product name "Diana Process Oil PW-100") was used.
[0096] [Hydrogenated block copolymer (D)] As the hydrogenated product of the block copolymer (D), a hydrogenated product of the block copolymer produced by the method described below was used.
[0097] [Production of hydrogenated block copolymer (D-1)] (1) Preparation of hydrogenation catalyst The hydrogenation catalyst used in the hydrogenation reaction of the block copolymer was prepared by the following method: 1 L of dried and purified cyclohexane was charged into a nitrogen-substituted reaction vessel, 100 mmol of bis(cyclopentadienyl)titanium dichloride was added, and an n-hexane solution containing 200 mmol of trimethylaluminum was added while thoroughly stirring, and the reaction was allowed to proceed at room temperature for about 3 days.
[0098] (2) Production of hydrogenated block copolymers Batch polymerization was carried out using a tank reactor with a jacket and a stirring device with an internal volume of 10 L. First, 6.4 L of cyclohexane and 75 g of styrene were added, and TMEDA was added in advance so that the number of moles of Li in n-butyllithium was 0.25 times the molar amount, and the number of moles of Li in the n-butyllithium initiator was 10 mmol. Polymerization was carried out at an initial temperature of 65 ° C., and after the polymerization was completed, a cyclohexane solution containing 470 g of butadiene and 380 g of styrene (monomer concentration 22% by mass) was continuously fed to the reactor at a constant rate over 60 minutes, and after polymerization, a cyclohexane solution containing 75 g of styrene (monomer concentration 22% by mass) was added over 10 minutes to obtain a copolymer (D-1').
[0099] The styrene content in the obtained copolymer (D-1') was 53 mass%, the styrene polymer block content was 15 mass%, the styrene content in the copolymer block (i.e., the copolymer block containing conjugated diene monomer units and vinyl aromatic monomer units) was 45 mass%, and the vinyl bond content was 23%.
[0100] The hydrogenation catalyst was added to the obtained copolymer (D-1') in an amount of 100 ppm in terms of titanium per 100 parts by mass of the polymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 75° C. To the obtained polymer solution, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer per 100 parts by mass of the hydrogenated block copolymer to obtain a hydrogenated block copolymer (D-1).
[0101] The weight average molecular weight of the hydrogenated block copolymer (D-1) was 160,000, and the hydrogenation rate of the butadiene double bonds contained in the hydrogenated block copolymer (D-1) was 99%. In addition, one of the tan δ peaks obtained by viscoelasticity measurement was present at -15°C.
[0102] [Polyorganosiloxane (E)] As the polyorganosiloxane (E-1), a master batch consisting of 50 mass % dimethylsiloxane and 50 mass % polypropylene (manufactured by DuPont-Toray Specialty Materials, product name "MB50-001") was used.
[0103] [Organic peroxide (F)] As the organic peroxide (F), a mixture of the following organic peroxide and the following crosslinking aid was used. Organic peroxide: 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane (manufactured by NOF Corporation, product name "Perhexa 25B") 100 parts by mass Crosslinking aid: 15 parts by mass of divinylbenzene (manufactured by Wako Pure Chemical Industries, Ltd.; hereinafter referred to as "DVB")
[0104] <Example 1> <Production of Composition> The extruder used was a twin-screw extruder (30 mmφ, L / D=74; Kobe Steel, "KTX-30") with an oil inlet in the center of the barrel. A two-thread screw with kneading sections before and after the inlet was used as the screw. The raw materials other than the softeners shown in Table 1 were mixed together in the composition ratios (parts by mass ratios) shown in Table 1, and then introduced into the twin-screw extruder (cylinder temperature 200°C) using a fixed quantity feeder. Subsequently, the softeners in the amount shown in Table 1 were pumped into the inlet in the center of the extruder, and melt extrusion was performed to obtain a thermoplastic elastomer composition.
[0105] <Production of injection molded products> The injection molding machine used was the "M150CL-DM" manufactured by Meiki Seisakusho Co., Ltd. The molding conditions were a resin temperature of 220°C and a mold temperature of 40°C. The thermoplastic elastomer composition obtained above was injection molded using a flat plate mold measuring 15cm long x 9cm wide and with a leather grain finish. Two types of flat plate molds with different grain shapes were used, and molded products with two types of roughness, normal grain (average arithmetic roughness Ra = 20μm) and fine grain (Ra = 6μm), were produced as molded body samples. The physical properties of the obtained thermoplastic elastomer compositions and molded samples were evaluated by the following methods. The results are shown in Table 1.
[0106] (1) MFR (g / 10 min) The melt flow rate of the thermoplastic elastomer composition obtained above was measured at 230° C. under a load of 1.2 kgf in accordance with JIS K7120.
[0107] (2) Shore A hardness measurement In accordance with JIS K6253, a press sheet having a thickness of 2 mm was prepared from the thermoplastic elastomer composition obtained above, and three of these press sheets were stacked to obtain a laminated sheet having a thickness of 6 mm, which was used as a measurement sample. The test sample obtained above was measured using a Shore A hardness tester. The value read 10 seconds after the pressure plate was brought into contact with the test piece was taken as the Shore A hardness (10 second value).
[0108] (3) Scratch resistance The molded body samples with the two types of roughness obtained above (normally textured molded body sample and finely textured molded body sample) were scratched with a pencil-type scratch hardness tester (Erichsen, 318 / 318S No.2) with a load of 10 N, 10 scratches each in the vertical and horizontal directions. The scratches in the central grid area were visually observed and evaluated. Evaluation was performed according to the following criteria. A: Almost no change in appearance due to scratches is observed. B: Slight changes in appearance due to scratches are observed. C: Changes in appearance due to scratches are observed. D: Significant change in appearance due to scratches.
[0109] (4) Texture (smoothness) The feel (smooth feel) was evaluated according to the following criteria when the surface of the molded sample obtained above was rubbed with the pad of the index finger. The smooth feel evaluation was performed by three people, and all the people gave the same evaluation results. A: Good (smooth feeling. No resistance felt when sliding a finger over it.) B: Slightly poor (not very smooth. Some resistance is felt when sliding a finger over it.) C: Poor (No smooth feeling. Resistance is felt when sliding a finger over the surface.)
[0110] <Examples 2 to 4 and Comparative Examples 1 to 6> Samples were produced and evaluated in the same manner as in Example 1, except that the raw materials used were changed to the composition shown in Table 1, and the grain shape of the molded body was molded into the grain shape shown in Table 1.
[0111] [Table 1]
[0112] <Evaluation Results> As shown in Table 1, the injection molded articles of Examples 1 to 4 are soft with low hardness, and have excellent scratch resistance and smooth feel. On the other hand, the molded articles of Comparative Examples 1 to 3 were not excellent in dry feeling, and the molded articles of Comparative Examples 4 to 6 were not good in either dry feeling or scratch resistance.
Claims
1. At least a part of a surface of a molded body is formed from a thermoplastic elastomer composition, and the arithmetic mean roughness (Ra) of the surface of the molded body is more than 0 and less than 20 μm; The thermoplastic elastomer composition comprises (A) a propylene-based polymer, (B) an ethylene-α-olefin copolymer containing ethylene and an α-olefin unit having 3 to 20 carbon atoms, (C) a softener, and (D) a hydrogenated product of a block copolymer having at least one block mainly composed of conjugated diene monomer units and at least one block mainly composed of vinyl aromatic monomer units.
2. 2. The molded article according to claim 1, wherein the thermoplastic elastomer composition comprises: (A) 100 parts by mass of a propylene-based polymer; (B) 45 to 300 parts by mass of an ethylene-α-olefin copolymer containing ethylene and an α-olefin unit having 3 to 20 carbon atoms; (C) 45 to 300 parts by mass of a softener; and (D) 100 to 400 parts by mass of a hydrogenated block copolymer having at least one block mainly composed of conjugated diene monomer units and at least one block mainly composed of vinyl aromatic monomer units.
3. The molded article according to claim 1 or 2, wherein the thermoplastic elastomer composition contains 2 parts by mass or more of (E) polyorganosiloxane.
4. The molded article according to any one of claims 1 to 3, wherein in the thermoplastic elastomer composition, a mass ratio (C / B) of (B) to (C) is greater than 0 and less than 3.
5. The molded article according to any one of claims 1 to 4, wherein the block mainly composed of conjugated diene monomer units of the hydrogenated block copolymer (D) constituting the thermoplastic elastomer composition is a copolymer block mainly containing conjugated diene monomer units and also containing vinyl aromatic monomer units.
6. The molded article according to any one of claims 1 to 5, wherein the thermoplastic elastomer composition is a dynamically heat-treated thermoplastic elastomer composition.
7. At least a portion of the ethylene / α-olefin copolymer (B) is crosslinked. Item 7. The molded article according to any one of items 1 to 6.
8. The molded article according to any one of claims 1 to 7, which is obtained by injection molding.
9. The molded article according to any one of claims 1 to 8, which is an automobile interior part.
Citation Information
Patent Citations
Thermoplastic elastomer sheet with decorative pattern and laminate constituted of the sheet
JP1994071751A
Thermoplastic elastomer laminate and automotive trim / interior parts
JP1997156053A
Thermoplastic resin molding, mold for injection-molding the molding, and injection molding method
JP2012086453A
Injection molding made of thermoplastic resin, and method for manufacturing the same
JP2012111127A
Injection-molded article
JP2014000770A